Statistical Population Reconstruction Using Wings from Harvested Northern Bobwhites Can Inform Management - Theron M. Terhune II; Kristen M. Malone; D. Clay Sisson; James A. Martin (National Quail Symposium Proceedings, 2017)
Despite the widespread collection wings from harvested northern bobwhite (Colinus virginianus) by state wildlife agencies and private entities, age-at-harvest information has been largely underutilized for guiding management decisions for this species. Statistical population reconstruction (SPR) techniques can use age-at-harvest information and provide a valuable tool for monitoring trends and the status of bobwhite (and other game bird) populations. However, SPR has not been applied to bobwhite. We evaluated the utility of statistical population reconstruction models, which have been applied successfully to other species (e.g., elk, Cervus elaphus; blacktailed deer, Odocoilues hemonius; and greater sage-grouse, Centrocercus urophasianus), to reconstruct annual abundance and demographic attributes for a bobwhite population in southwest Georgia. During 1998 – 2016, we collected wings from harvested birds (n = 17,448; nannual = 969 ± 104) in conjunction with survival information from mark-recapture. We derived independent estimates of fall abundance from the same site using covey call counts and a standardized measure of hunting success (coveys moved per hour). SPR models suggested that population change was stable (λ = 1.00; CV = 0.19) compared to moderate population growth (λ = 1.05; CV = 0.29) indicated by the covey call quadrat method. Abundance estimates from SPR and covey call counts were moderately correlated (r = 0.48) with only 3 out 18 years statistically different. Abundance estimates from SPR and hunting success (coveys moved per hour) was highly correlated (r = 0.86). SPR provides valid, conservative abundance estimates for bobwhite age-at-harvest data. Therefore, we endorse the use of SPR for bobwhites where age-at-harvest, hunter effort and another source of auxiliary data are readily available. As such, given that the collection of harvested wings is simple and low cost, we recommend managers and state agencies consider incorporating this technique into their management program.
Keywords: age; harvest; Colinus virginianus; northern bobwhite; statistical population reconstruction; wing data